Nature's clocks [electronic resource] : how scientists measure the age of almost everything - Macdougall, J. D. , 1944- (University of California Press, 2008)
Examining radiocarbon (C-14) dating - the best known of these methods - and several other techniques that geologists use to decode the distant past, this book unwraps the last century's advances